Penetapan Sanksi Qishas Terhadap Tindak Pidana Main Hakim Sendiri Dalam Perspektif Hukum Pidana Islam - Batu Bara, asmiah; Nasution, Muhammad Arsad; Harahap, Risalan Basri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The problem in this study is regarding vigilante sanctions in the perspective of Islamic criminal law. Because there are no regulations or laws governing vigilante sanctions. This type of research is field research using normative legal and empirical legal approaches. The data source for this research comes from primary data and secondary data. The primary data source is the Investigator from the Criminal Investigation Unit of the Mandailing Natal Resort Police and the secondary data source is books, data, journals and documents. The data collection technique used consisted of interviews, observation, and documentation. Data analysis techniques were descriptive qualitative. The results of this study are that the vigilante sanction in the Mandailing Natal Resort Police area has already been stipulated in accordance with Article 170 of the Criminal Code, but in terms of implementation it has never been carried out because the Resort Police considers that the victim of vigilantism is usually because he was the perpetrator of a previous crime, so the perpetrator is considered as an enemy of society as well. Vigilance in Islamic criminal law already has provisions in which the vigilante is subject to qishas sanctions, but if the victim's family forgives the perpetrator, the sanction is replaced with a diyat.